Information and Computer Literacy - Marcen, Benjamin (Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes, 2026)
In today's digitalized world, information literacy is a key skill that enables the effective and confident use of technology. In this chapter we will explore all the aspects of information and computer literacy that are indispensable for the contemporary life. We will start with basic steps such as using and customizing your desktop, working with the taskbar and icons, and managing files and folders. We will also learn how to use explorer, lock, and compress files and manage various useful applications. We will continue with the more advanced use of Word and Excel. We will look in detail at creating and formatting text, using cross-references, creating tables, using functions and entering graphs. In addition, we will explore user communication, the use of different internet browsers, and online communication applications such as Microsoft Teams and Zoom.